Two-dimensional organic tin Halide Perovskites with tunable visible emission and their use in light-emitting devices - Lanzetta,Lopez L; Marin-Beloqui,JM; Sanchez-Molina,I; Ding,D; Haque,SA (ACS Energy Letters, 2017)
Hybrid organic lead trihalide perovskites continue to generate significant interest for use in optoelectronic devices such as solar cells and light-emitting devices. However, the toxicity of lead is considered one of the main obstacles to the commercialization of this technology. Although challenging, the replacement of lead by tin is currently the most promising alternative. Herein, we explore a class of low-dimensional, lead-free perovskite materials (2D (PEA)2SnIxBr4–x, where PEA ≡ C6H5CH2CH2NH3+) with tunable optical properties in the visible region of the spectrum. Specifically, we show that 2D (PEA)2SnI4 perovskite exhibits superior photoluminescence properties to conventional 3D CH3NH3SnI3 and that (PEA)2SnI4 can act as a sensitizer on mesoporous TiO2. We go on to demonstrate visible (∼630 nm) electroluminescence from a device employing a (PEA)2SnI4 emitter sandwiched between ITO/PEDOT:PSS and F8/LiF/Al as hole and electron injection electrodes, respectively. These devices reach a luminance of 0.15 cd/m2 at 4.7 mA/cm2 and an efficacy of 0.029 cd/A at 3.6 V. This proof-of-principle device indicates a viable path to low-dimensional, lead-free perovskite optoelectronics.